Forgiving, listening, waiting: Ethics of solidarity in Kosova’s movement of civil resistance in the1990’s - Arbër Jashari (Kosova Anthropologica)
As the breakup of Yugoslavia in the early years of the 1990’s turned violent and pitted constituent republics against one-another, an overwhelming majority of ordinary people in Kosova embraced a societal-wide movement of civil resistance to the oppressive policies adopted by the state of Serbia. Kosova's non-violent movement, which ran for almost a decade, emerged upon strong moral foundations stemming from tradition and was characterized by the invocation of an ethics of solidarity. In this paper, I elaborate on three concrete ethical and affective practices in which ordinary people were invested during this period – forgiving, listening, and waiting. I argue that a heightened degree of ethical comportment was central to the conception, as well as to the life of, the non-violent movement.